Effects of soil ameliorant composition on soil properties and chili (Capsicum annuum L.) yield in inceptisols Jatinangor - Baiq Azizah Haryantini; Yosef Situmorang; Anne Nurbaity; Tualar Simarmata (Jurusan Agroteknologi, 2023)
Inorganic fertilizers have an important role in improving the productivity of chili plants, but continuous use will cause soil quality to decline. The use of ameliorant is expected to improve soil quality. This experiment was aimed to find out the best effect of ameliorant composition and dose on organic-C, soil pH, population of phosphate solubilizing bacteria, and yield of chili plant in Inceptisols Jatinangor. The research was conducted in plastic house of Agricultural Faculty of Padjadjaran University on January – Mei 2018. The design experiment was factorial randomizedblock design which consisted of two factors with three replications. The first factor was ameliorant composition consisting of four levels (a1 = 80% cow manure + 20% Biochar Coconut Shell ; a2 = 95% Composition a1 + 5% Dolomite and Guano ; a3 = 90% Composition a1 + 10% dolomite and guano; a4 = 85% composition a1 + 15% dolomite and guano), and the second factor was ameliorant dose consisting of four levels (t0 = 0 t ha-1 ; t1 = 2 t ha-1 ; t2 = 4 t ha-1 ; t3= 6 t ha-1). The results showed that there were no interaction between composition and dose of ameliorant to organic-C, soil pH, population of phosphate solubilizing bacteria, and yield of chili on Inceptisols Jatinangor. The 4 t ha-1 of ameliorant dose increased organic-C, soil pH, population of phosphate solubilizing bacteria, and yield of chili plant by 44,9%.ABSTRAK Pupuk anorganik meningkatkan produktivitas tanaman cabai, namun penggunaan terus menerus akan menyebabkan kualitas tanah menurun. Penggunaan amelioran diharapkan dapat memperbaiki kualitas tanah. Penelitian ini bertujuan untuk mengetahui pengaruh komposisi dan dosis amelioran terbaik terhadap C organik, pH tanah, populasi bakteri pelarut fosfat, dan hasil tanaman cabai di Inceptisols Jatinangor. Penelitian dilakukan di rumah plastik Fakultas Pertanian Universitas Padjadjaran bulan Januari – Mei 2018 menggunakan rancangan acak kelompok faktorial terdiri dari dua faktor dengan tiga ulangan. Faktor pertama adalah komposisi amelioran yang terdiri dari empat taraf (a1 = 80% kotoran sapi + 20% biochar batok kelapa; a2 = 95% komposisi a1 + 5% dolomit dan guano; a3 = 90% komposisi a1 + 10% dolomit dan guano; a4 = 85% komposisi a1 + 15% dolomit dan guano), dan faktor kedua adalah dosis amelioran yang terdiri dari empat taraf (t0 = 0 t ha-1 ; t1 = 2 t ha-1 ; t2 = 4 t ha-1 ; t3= 6 t ha-1). Hasil penelitian menunjukkan bahwa tidak terdapat interaksi antara komposisi dan dosis amelioran terhadap C-organik, pH tanah, populasi BPF, dan hasil cabai pada Inceptisols Jatinangor. Dosis amelioran 4 t ha-1 meningkatkan C-organik, pH tanah, populasi BPF, dan meningkatkan hasil tanaman cabai sebesar 44,9%.